Monitoring Methicillin-Resistant Staphylococcus Strains in the Moscow Medical and Surgical Center using Molecular-Biological Methods - T. S. Skachkova; M. N. Zamyatin; O. A. Orlova; N. A. Yumtsunova; N. N. Lashenkova; V. S. Fomina; V. G. Gusarov; Yu. V. Mikhaylova; A. A. Shelenkov; E. N. Goloveshkina; V. G. Akimkin (Эпидемиология и вакцинопрофилактика)
Relevance. Staphylococci are one of the most common pathogens in the etiological structure of nosocomial infections. Methicillinresistant staphylococci are resistant to the main groups of antibiotics and are one of bacteria that pose the greatest threat to human health according to the World Health Organization. The introduction of modern molecular biological methods in the monitoring of methicillin-resistant staphylococci is necessary for the rapid and accurate identification of microorganisms, monitoring the epidemiological situation and studying the need for anti-epidemic measures. Aims. Аnalysis of the results of monitoring methicillinresistant staphylococcus strains using molecular biological methods in a multidisciplinary hospital in Moscow for one year. Materials and methods. Single-center observational study with a one-year follow-up period (December 2016 to December 2017). The research included a molecular-biological analysis of biological material from 240 patients with signs of infection and washings samples (n=250) from the objects of the hospital environment. The whole genome sequencing was carried out for 24 samples, isolated from patients with different forms of staphylococcal infection and washings from a hospital environment. DNA detection of methicillin-resistant strains was performed using the «AmpliSens®MRSA-screen-titer-FL» reagent kit. Sequencing was performed on an Illumina HiSeq1500 instrument using the IlluminaHiSeq PE RapidClusterKit v2 and IlluminaHiSeqRapid SBS Kit v2. Results. DNA of methicillin-resistant staphylococci were detected in 6.3% of blood samples from patients with signs of infection and in 42.4% of washings from the objects of the hospital environment. The results of PCR of washing samples showed that DNA of methicillin-resistant coagulase-negative staphylococci were detected much more often than MRSA (p <0.001). DNA of methicillin-resistant staphylococci were detected more often in the intensive care and intensive care units compared with the hematology and surgical departments (p <0.001). The examine samples of Staphylococcus aureus belonged to 6 different sequence types (ST-5, ST-7, ST-8, ST-22, ST-30 and ST-5555) and 8 spatypes (t008, t021, t091, t1062, t12437, t1544, t223, t4573). As a result of monitoring, an isolate with a new allelic profile was found. Today it has been assigned the number ST5555. The predominant type of staphylococcal mec cassette was the type IV SCCmec cassette. Conclusion. Due to the widespread distribution of methicillin-resistant strains and the identification of epidemiologically significant genetic lines of staphylococci, it is necessary to conduct regular monitoring, take measures to limit the spread of such strains and introduce modern molecular biological methods for quick and accurate identification.